Food waste assessment: Standards and actions to promote circularity in Peru - Huiman Cruz, Alberto (2024)
Population growth generates a higher demand for food and, thereby the waste of larger quantities of food. The fight against this problem has been initiated in several countries through strict regulations that manage food waste: Peru has made proposals related to the use of food waste, however, they were ineffective when it became evident that there was a lot of waste The objective of this article is to analyze the management of food waste in Peru and the world, both in terms of regulations and situation; for this purpose, a bibliographic review was carried out taking into account the guidelines of circularity in food. The results obtained show deficiencies in the Peruvian and world regulatory framework, with the exception of Europe. It was found that the generation of food waste is abundant worldwide, especially in the hotel, restaurant and cafeteria sector, with portion size being the main cause. The countries coincide in their concern for the increase in waste and seek to frame themselves in the circularity model, in the case of Peru, this implies modifying and improving regulations with the participation of the actors involved. In view of this, a vision of sustainability is proposed in which the agricultural sector, the local economy, the supply chain, and technology intervene as factors that guarantee a sustainable food industry; as well as the legislative initiatives that seek to reduce food waste.